Implementasi Program Keluarga Harapan (Pkh) Dalam Upaya Penanggulangan Kemiskinan Di Kecamatan Bojonegoro - Putri1, Nadia Afriza; Purnaweni, Hartuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Abstract: In order to reduce the amount of poverty in Bojonegoro District, the government has implemented Program Keluarga Harapan (PKH) since 2008. PKH is a Conditional Cash Transfers (CCT) program, which is a conditional assistance program given to very poor households (RTSM) by giving obligations to PKH beneficiary families (KPM) to fulfill PKH commitments. This study aims to determine the implementation of PKH in Bojonegoro District. The method used is by conducting purposive sampling interviews with the implementers including the PKH Coordinator for the West and North Regions of Bojonegoro Regency, PKH Coordinator for the East and South Regions of Bojonegoro Regency, Coordinator of PKH Facilitator in Bojonegoro District, PKH Facilitator in Bojonegoro District, KPM PKH in Bojonegoro District and documentation. The research method is descriptive qualitative. The results of this study found the fact that the implementation of PKH in the context of alleviating poverty in Bojonegoro District had been carried out according to the provisions and regulations. However, in practice, there are various problems that affect the quality of PKH implementation, namely the lack of information related to the distribution of aid, the uneven distribution of complementary assistance, the non-fulfillment of the tasks of PKH facilitators to conduct home visits due to the lack of assistants, and the lack of KPM knowledge about the goals of PKH. There are many factors that influence the implementation of PKH in Bojonegoro District, including communication and coordination between PKH implementing officials, human resources, the character of PKH beneficiary families and also the bureaucracy. The recommendations that given are the Bojonegoro Regency PPKH Team needs to improve the coordination and communication with the channeling bank, improve performance to verify the distribution of complementary assistance to KPM, increase the number of PKH facilitators in Bojonegoro District and increase socialization about the goals of PKH to KPM.